TRANSFORMASI IDENTITAS KEAGAMAAN SANTRI MELALUI MEDIA SOSIAL DI MADRASAH DINIYAH SALAFIYAH RIYADLOTUL UQUL SUMBERASIH PROBOLINGGO - Hidayat, Sofian; Jadid Khadavi, M. (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
This research aims to determine the influence of social media on the religious identity of students at Madrasah Diniyah Salafiyah Riyadlotul Uqul located in Banjarsari Village, Sumberasih District. With the development of information technology and the increasing accessibility of social media, students' religious identity can be influenced by various factors related to the digital world. This study uses a qualitative method with a phenomenological approach to explore students' experiences in interacting with social media and how it affects their religious understanding and practices. Student have a tendency to openly accept various interpretations of religion, although at the same time they have difficulty filtering information in accordance with Salafi teachings. Participants in this study included the head of the Diniyah Madrasah, teachers and student. The findings of this study make a significant contribution to understanding the role of social media in shaping religious identity in Salafiyah Islamic schools. In addition, the findings also provide insights in developing educational strategies and fostering a healthy religious identity in this digital era.